Algorithmic Medias Res: YouTube Shorts, Affordances, and the Reconfiguration of Agency in Digital Consumption Practices - Rama, Ilir (Italian Sociological Review, 2026)
Digital platforms have influenced and reshaped the consumption of culture, entertainment, and news through their sociotechnical nature and algorithmic systems. Scholarly approaches to studying content flows within these environments have emphasized various perspectives: some focus on algorithmic systems’ power in structuring environments that aggregate similar viewpoints, while others highlight user agency in resisting and repurposing platforms, still others focus on combinations of the two. This paper contributes to this debate through a longitudinal analysis of YouTube, based on data from 107 Italian users, comprising over three million data points across a decade. By triangulating users’ searches and consumed content, this article considers how individuals navigate algorithmic recommendations while accounting for platform-level changes such as the introduction of YouTube Shorts. Findings reveal users increasingly consumed content while relying less on search features and more on algorithmic systems, demonstrating how new affordances can restructure user agency beyond algorithmic optimization alone. Rather than viewing agency as residing with either platforms or users, findings concur in pointing to how platforms frame agency, but it is ultimately co-constructed by technical, social, and cultural components. This in turn requires methodological approaches that can capture the evolution of the platform and the affordances framing digital consumption within it.